Pengelolaan Kawasan Mangrove Berbasis Masyarakat di Kecamatan Sayung, Demak - Nasution, Muhammad Yazid Alwi; Wijaya, Holi Bina (Teknik PWK (Perencanaan Wilayah Kota), 2024)
This research is a study conducted in four villages of Sayung Coast, Demak Regency, Central Java which consists of Surodadi, Timbulsloko, Bedono, and Sriwulan. The condition of the Sayung Coastal Area is often hit by tidal floods due to abrasion, which causes villages to lose natural protection along with less controlled mangrove territory. Mangrove Associations were initiated in 2004 as a form of prevention against disasters and for mangroves development. The purposes of this study are to study and find out how the community-based mangrove management system and its benefits are in Sayung Coast. The approach concept used is the application of Community Based Mangrove Management (CBMM) using qualitative descriptive methods. The analytical technique used to obtain data is case study analysis techniques which forms some data typologies. The analysis results collected, reduced, and served show that there is a data variety of community-based mangrove management systems and some data variety of management benefits in each of the four villages. The existence of such management is indicated by the form of management stages (planning, implementation, and supervision). Awareness of the environment and length of stay motivates the community to participate. Most forms of participation rely on energy and thought.